Recent advancements in nonwoven bio-degradable facemasks to ameliorate the post-pandemic environmental impact. (23rd November 2021) - Khan, Junaid; Momin, Syed Abdul; Mariatti, M; Vilay, V; Todo, M
Abstract: Plastics have become a severe risk to natural ecosystems and human health globally in the last two decades. The outbreak of the coronavirus pandemic, which led to the manufacturing and use of billions of facemasks made from non-biodegradable and petroleum-derived polymers has aggravated the situation further. There is an urgent need to develop bio-degradable facemasks with excellent filtration efficiency and antimicrobial characteristics using scalable technology. This review article aims to provide the fundamentals of mask technology, its environmental footprint, facemask's lifecycle assessment, conventional manufacturing routes, and state-of-the-art reports on using bio-degradable polymers for facemask applications. The article also focuses on the current challenges of the conventional facemask and the prospects of an ideal facemask that could significantly reduce the ill effects of petroleum-based polymers. The review includes concise information on the basics of polymer biodegradation and standardized tests to evaluate biodegradability. The use of currently available facemasks has been an effective measure to curb the infection rate, however, is a threat to the environment. Reusing the facemask after decontamination is not a solution from a safety perspective as cloth-based facemasks have lower filtration efficiencies which get further reduced with the washing cycle necessitating a shift towards biodegradable facemask. Systematic information is provided through this article to stimulate research on a bio-degradable facemask with excellent filtration efficiency, antimicrobial properties, and cost-effectiveness for global usage.